2021
DOI: 10.34204/jiafe.v7i2.3172
|View full text |Cite
|
Sign up to set email alerts
|

Identifikasi Persepsi Mahasiswa Dalam Mengambil Sertifikasi Akuntan Profesional

Abstract: ABSTRAKTujuan penelitian ini ingin menguji persepsi niat mahasiswa untuk mengambil sertifikasi akuntan profesional sebagai Chartered Accountant (CA), Certified Internal Auditor (CIA), dan Certified Public Accountant (CPA). Subjek penelitian adalah mahasiswa program studi akuntansi Universitas Pekalongan. Sampel penelitian diambil dengan menggunakan random sampling pada mahasiswa Universitas Pekalongan. Data penelitian dikumpulkan dengan penyebaran kuesioner. Teknik analisis data menggunakan uji validitas, uji … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…If someone has a positive outlook _ that certification will give benefit them, then Thing this will push their interest to follow the certification profession. This thing by several results researchers that attitude takes to effect positively to intention student for taking certification accountant professionals (Affifah et al, 2021;Dewi et al, 2019;Endayani & Witono, 2021). Based on the exposure above, then could formulate a hypothesis as follows: H2: _ Attitude take to effect positively to interest student accountancy follow certification profession.…”
Section: The Influence Of Attitudes On the Interest Of Accounting Stu...mentioning
confidence: 92%
See 1 more Smart Citation
“…If someone has a positive outlook _ that certification will give benefit them, then Thing this will push their interest to follow the certification profession. This thing by several results researchers that attitude takes to effect positively to intention student for taking certification accountant professionals (Affifah et al, 2021;Dewi et al, 2019;Endayani & Witono, 2021). Based on the exposure above, then could formulate a hypothesis as follows: H2: _ Attitude take to effect positively to interest student accountancy follow certification profession.…”
Section: The Influence Of Attitudes On the Interest Of Accounting Stu...mentioning
confidence: 92%
“…Whereas attitude no take affect students' intention to take accounting professional certification. However, the research of Affifah et al, (2021) concluded that attitude affects the intention of students to follow certification accountant professional. Constraints are also one of the factors that influence the interest of accounting students to take the professional certification.…”
Section: The Development Of the Number Of Iai Members In 2016 -2019 I...mentioning
confidence: 99%